Quality of the ewes' milk as a raw material in the dairy industry in the Republic of North Macedonia : Kvaliteta ovčjeg mlijeka kao sirovine u mliječnoj industriji u Republici Sjevernoj Makedoniji - Dimitrovska, Gordana (Array, 2020)
This study is based on analyzing physico-chemical and microbiological characteristics of ewe milk from three different regions, which is used as a raw material in dairy industry of North Macedonia. All milk samples (n=123) were collected on dairy reception points of dairy industry in Pelagonia region, in a period of six (6) months. The average values for chemical composition of milk were in the range as follows: 6.83±0.22% to 7.68±0.36% for milk fat, 5.52±0.09% to 6.06±0.23% for proteins, 4.62±0.08% to 4.79±0.05% for lactose, 11.16±0.11% to 1.51±0.24% for non-fat dry matter (NFDM), -0.561 to -0.543oC for freezing point and 8.61±0.4 oSH to 8.88±0.47oSH for titrable acidity. The microbiological and hygienic status of examined ewe milk samples was of poor hygienic quality. The average value of the examined samples for somatic cell count ranged from 753.333 cfu/mL to 1.125.000 cfu/mL and the average number of total bacteria count was from 532.444 cfu/mL to 1.986.222 cfu/mL.